Back Cover: TEMPO‐Oxidized Cellulose Cross‐Linked with Branched Polyethyleneimine: Nanostructured Adsorbent Sponges for Water Remediation (ChemPlusChem 9/2015). Issue 9 (1st July 2015) - Melone, Lucio; Rossi, Bianca; Pastori, Nadia; Panzeri, Walter; Mele, Andrea; Punta, Carlo
<x xml:space="preserve">Abstract</x> The cover picture shows the preparation of adsorbent sponges for water remediation from TEMPO‐oxidized cellulose nanofibers (TOCNF) and branched polyethyleneimine (bPEI; 25 kDa). The cross‐linking occurs between the carboxylic groups of TOCNF and the primary amino groups of bPEI during the thermal treatment of freeze‐dried TOCNF‐bPEI composites. These materials combine good mechanical stability in water, compared to TOCNF, with interesting performance in removing both heavy metals and phenolic derivatives from water. More details can be found in the Full Paper by Lucio Melone, Carlo Punta et al. on page 1408 in Issue 9, 2015. (DOI: 10.1002/cctc.201500145).